Prediksi Produksi Padi di Kabupaten Sumenep Menggunakan Metode Single Exponential Smoothing - Amaliyatul Hasanah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Rice is a source of carbohydrates which is the staple food of Indonesian people. The increase in human population means that Indonesia has to import rice from abroad to meet national food needs. Domestic rice production is not the same every year and with the conversion of agricultural land into industrial and residential areas, rice productivity has decreased. Sumenep Regency is one of the rice food production areas which is not the same every year, so forecasting is necessary to predict rice production in Sumenep Regency. Rice production forecasting can be used as a reference for increasing rice production in Sumenep district. The method used to forecast rice production in Sumenep district is the Single Exponential Smoothing method. The data used is rice production data in Sumenep district in 2005-2022. The results of forecasting rice production in Sumenep district obtained forecasts for rice production in 2023 of 203132.55 tonnes with a MAPE value of 11.243% with α=0.3.